Palmul-Tang, a Korean Medicine, Promotes Bone Formation via BMP-2 Pathway in Osteoporosis - La Yoon Choi; Mi Hye Kim; Yeon Kyung Nam; Ju Hee Kim; Hea-Young Cho; Woong Mo Yang (Frontiers Media S.A., 2021)
Osteoporosis is a common skeletal disease in post-menopausal women. Palmul-tang, an herbal medicine, has been treated for gynecological disease such as anemia, anorexia, anti-fatigue, unspecified menstruation and female infertility in East Asia. In this study, ameliorative effects of Palmul-tang soft extracts (PMT), a Korean Medicine, on osteoporosis were investigated. Ovariectomized (OVX) osteoporotic ICR mice were intragastrically administrated PMT for 4 weeks. The level of bone mineral density (BMD) was analyzed in bone tissues by dual X-ray absorptiometry. The bone medullary cavity and deposition of collagen were investigated by histological analysis. In addition, the BMP-2 signaling-related molecules, osteoblastic differentiation and formation markers, were determined in femoral tissues. The levels of BMD and bone mineral content were significantly increased in tibia, femurs and LV by treatment of PMT. PMT replenished bone marrow cavity and increased collagen deposition in bone marrow cells of femur. In addition, administration of PMT recovered serum ALP, bALP, osteocalcin and calcium levels in osteoporotic mice. Moreover, PMT treatment up-regulated the expressions of BMP-2, RUNX2 and OSX with its downstream factors, ALP, OPN and BSP-1, in the femoral tissues. Taken together, PMT restored the bone minerals and improvement of bone integrity by bone-forming BMP-2 signaling pathway. These results demonstrate that PMT could be an ameliorative agent for osteoporosis.